Baseline fibroblast growth factor 23 is associated with long-term mortality in ST-elevation myocardial infarction—results from the augsburg myocardial infarction registry - Schmitz, Timo; Wein, Bastian; Heier, Margit; Peters, Annette; Meisinger, Christa; Linseisen, Jakob (Frontiers in Cardiovascular Medicine, 2023)
The aim of this study was to investigate the association between inflammatory plasma protein concentrations and long-term mortality in patients with ST-elevation myocardial infarction (STEMI).For 343 STEMI patients recorded between 2009 and 2013 by the population-based Myocardial Infarction Registry Augsburg, 92 inflammatory plasma proteins were measured at the index event using the OLINK inflammation panel. In multivariable-adjusted Cox BW, MH, AP and JL contributed to data acquisition and revised the manuscript.